2020
DOI: 10.1002/adom.202001040
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum for Near Infrared Plasmonics: Amplified Up‐Conversion Photoluminescence from Core–Shell Nanoparticles on Periodic Lattices

Abstract: Aluminum (Al) is known as a plasmonic material effective in a wide frequency range up to the ultraviolet, while its plasmonic properties in the near infrared region have been less explored. In this study, up‐conversion (UC) photoluminescence is amplified by using an Al nanostructure to demonstrate that Al is a useful plasmonic material in the near infrared region as well. A periodic lattice of Al nanocylinders is selected as a plasmonic nanostructure, where the size of nanocylinder and the period of the lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…21 The central cyclohexenyl chloro group of CySO is modified with the hydroxyl group of 4-(1,2,2-triphenylethenyl)phenol to afford CyTSO. 35 The final products CySO and CyTSO are confirmed by 1 H NMR, 13 C NMR, and mass spectra.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…21 The central cyclohexenyl chloro group of CySO is modified with the hydroxyl group of 4-(1,2,2-triphenylethenyl)phenol to afford CyTSO. 35 The final products CySO and CyTSO are confirmed by 1 H NMR, 13 C NMR, and mass spectra.…”
Section: Resultsmentioning
confidence: 85%
“…Lanthanide-doped upconversion nanoparticles (UCNPs) are photon conversion materials from NIR to visible wavelengths that has been used in 3D bioimaging, [1][2][3] photodynamic therapy, 1,2 solar energy harvesting, 4,5 and security printing [6][7][8] due to unique advantages such as low toxicity, deep light penetration, large anti-Stokes shift, and high stability. Although many promising achievements have been made in structural engineering and luminescence modulation, [9][10][11][12][13][14][15] the low luminance of UCNPs still restricts their practical application. The fundamental limitation is mainly due to the parity-forbidden nature of 4f electronic transitions in lanthanide ions, which results in a low extinction coefficient and a narrow absorption band.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the spatial organization as well as the relative distance and orientation of plasmonic antennas and upconverting NCs is currently better controlled for nondispersible nanostructures compared to dispersible ones. Nondispersible plasmonic structures mostly rely on patterned and unpatterned plasmonic films, as well as porous metal films, but also in conjunction with opal-structured photonic crystals. , A large variety of dispersible plasmonic nanostructures have also been reported (e.g., upconverting NCs decorated with plasmonic NPs, plasmonic NPs decorated with upconverting NCs, the growth of plasmonic shells on upconverting NCs, or the growth of Ln-doped shells on plasmonic NPs), , but to date many lead to only limited enhancement or quenching. This is due to the difficulty in precisely controlling important structural properties such as (i) spatial organization, (ii) tunable interparticle distance, and (iii) directionality of dispersible plasmonic structures.…”
Section: Enhancing the Generation Rate Gmentioning
confidence: 99%
“…Aluminum is the most abundant metal in the Earth’s crust and is widely used in water treatment, printing fabric, optics, , and catalysis . It is reported that aluminum is also a suitable material for plasmonic antennas for its high luminescence efficiency . The research on the mechanism of the enhancement of photoluminescence by aluminum has not stopped. , In addition, aluminum complexes such as aluminum oxynitride and aluminum borate are highly fluorescent .…”
Section: Introductionmentioning
confidence: 99%